Power distribution, performance changes and bioelectrical impedance properties during the preparation period of professional cyclists - Giorgi, A.; Vicini, M.; Bonifazi, M.; Gatterer, H. (Journal of Science and Cycling, 2017)
Introduction Athletic training improves exercise performance and modifies body composition. The influence of training volume and intensity during the general preparation period on performance and body composition has not been extensively studied in cyclists. Thus, this study aimed to investigate performance changes as well as changes in the body composition and bioelectrical impedance properties during a three-month training period with varying training volume and intensity.